Structure and semantics nominations of tax in the old-russian-ukrainian language (XI–XIII centuries) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article devoted to the nominations of tax sphere in the old-russian-ukrainian language (XI–XIII centuries). It gives a detailed analysis of words that indicate the nominations of the process taxation. Specifically addresses the question their etymology and their division into thematic groups. Scientists studied nominations of tax, including J. Varbot, T. Krehno, V. Nimchuk, T. Tsymbal, O. Chorna etc. The attention of researchers attracted only some partial issues related titles taxes, but there are still a number of unresolved questions about the history of the formation the nominations of tax sphere in general.The work allocated to the following groups nominations of tax sphere: nominations of taxes (general taxes on the population, taxes on the performance of certain services, customs duties), subjects of the tax process (collectors, tax payers) and places of collection of obligatory payments. Specifically addresses the question how each nominations formed, from the words which it originates and what it means. Common features of word formation nominations of tax sphere considered. The nominations of tax sphere and fees – a lexical and semantic group in the texts of the XI–XIII centuries, which covers the types of compulsory collection of objects of taxation from the population to the state treasury or in favor of the prince for various services, including transportation of goods across the border or internal customs bonds. The nominations subjects of taxation covering vocabulary, which indicates the persons related tax issues, which are the subject of or transfer tax. Appellations of tax collection called premises, institutions or territory in which the process of direct taxation. Often, the nominations of tax sphere in this language period derived from verbs and nouns. Morphological derivation method used most often, mostly using suffixes. The nominations of tax sphere and fees occupy an important place in the history of language, as it indicates the state of development of trade and economic relations, present a social and state system and reflect the progress of mankind at a particular historical stage. The present study provides a starting-point for further research in the history of the nominations of tax sphere. The obtained  results  enable  further  investigation  of  the  peculiarities the creation of tax nominations and their further historical analysis.
Keywords: tax; capitation; subjects of taxation; suffixal formants; confix; derivatives